STUDY OF CLIMATE CHANGE HAZARDS USING THE CLIMATE HAZARD INDEX IN INDONESIA - Wir, Joko Wiratmo; Robbani, Ismail; Susandi, Armi (Fakultas Ilmu dan Teknologi Kebumian (FITB), Institut Teknologi Bandung (ITB), 2024)
Climate change is a serious problem for the world. It causes significant impact on ecosystems and people in all parts of the world’s continents and oceans and poses grave risks to human health, global food security and economic development. One of the steps to reduce climate change disasters is climate risk management. Climate Risk Index (CRI) is a quantitative calculation of many climate risks with thresholds specific to extreme weather and climate events that cause disasters. One of the stages in preparing the CRI is to determine a hazard valuation or Climate Hazard Index (CHI). Because the climatic conditions in Indonesia vary with rainfall, it is necessary to conduct a study to determine the CHI associated with this variable.Therefore, in this study, climate hazards that are analyzed are limited to rainfall-related hazards, which are drought and extreme rainfall events. Then the constituent components of the CHI studied are the drought index and the extreme rain index. This hazard study shows an increasing trend in each of the CHI constituent component indices with a very high frequency of hazard events occurring frequently from 1995 to 2021. June was the month that had the highest average CHI among other months throughout 1962 -2021. In terms of spatial patterns, CHI is extreme in the Indonesian region with local and equatorial rainfall patterns. Whereas in the monsoon pattern, CHI is in the medium-very low range. Furthermore, CHI can be influenced by several factors, one of which is forest land cover. The results show that when the loss of forest land cover increases, the CHI value and its component index will also increase in the short term. Key words: Hazard, Climate change, Climate Hazard Index, Indonesia